Calculations of Gabor Lens Having Two Glaser Field Distributions - Al-Ghuraibawi, Azhar O. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present computational work is focused on investigating some properties of Gabor lens. The Gabor lens under consideration consists of two fields, electrostatic and magnetic. The Glaser field model is assumed to represent each field along the optical axis. Under zero magnification condition the trajectory of charged particles along the axis of Gabor lens has been computed. The results have shown that a lens of short focal length and hence high refractive power can be achieved